THE OPERATIONAL IMPACTS OF THE U.S. – INDONESIA STRATEGIC PARTNERSHIP ON THE JOINT MILITARY EXERCISES GARUDA SHIELD - Montolalu, Reynaldo Rudy Kristian; Perwita, Anak Agung Banyu; Sudibyo (Indonesian Association for International Relations, 2023)
Indonesia's increasingly strategic condition in the region has made the U.S. interested in cooperation that can better accommodate the two countries' national interests. Both countries established a Strategic Partnership which one of the objectives stipulated in the defense cooperation implemented through bilateral military exercises. Of the many militaries’ cooperation, the two countries have carried out, the author takes the case study of the Joint Military Exercise Garuda Shield, which is increasingly transforming from a peace operation training activity into a form of a military operation that tends to increase operationally. Through qualitative method, the research data were obtained from informants that had been previously determined. The result shows that the national interest of both countries was influenced by domestic and international factors, resulting in a shared interest that was projected in the Indo – Pacific region. The Strategic Partnership acts as the medium for both states to reach these interests, one of which by conducting bilateral military exercises. The U.S. – China rivalry factor has also driven Indonesia and the U.S. to interact in defense cooperation closer.